Model Pembelajaran Kooperatif Jigsaw Berbantuan Media Video Meningkatkan Hasil Belajar IPS Siswa Kelas IV Sekolah Dasar - Ni Putu Suryanita SP; Ni Nyoman Kusmariyatni (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
Lack of teacher ability to create fun learning and be accompanied by interesting learning media. This study aims to analyze the Jigsaw cooperative learning model assisted by video media to improve the learning outcomes of fourth-grade elementary school students. This type of research is classroom action research which is carried out in two cycles. Each cycle consists of stages of planning, implementing actions, observing and evaluating, and reflecting. The implementation of the action in each cycle is three meetings. The subjects of this study were students of class IVA, totaling 26 people. Data collection in this study was carried out by the test method. Data were analyzed by descriptive statistical analysis method. The results showed that in the first cycle the average social studies learning outcomes were 80,77 in the high category. Furthermore, in the second cycle, the average social studies learning outcomes were obtained at 86,37 in the high category. Based on the calculation of the gain score, the quality of improving social studies learning outcomes in the first cycle was 0,16 with a low predicate and the second cycle was 0,46 with a moderate predicate. Based on the results of this study, it can be concluded that the application of the Jigsaw-type cooperative learning model assisted by video media can improve social studies learning outcomes for fourth-grade elementary school students.